Investor financial literacy in the workplace - Jill E. Fisch; Tess Wilkinson-Ryan; Kristin Firth (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
The dramatic shift from traditional pension plans to participantdirected 401(k) plans has increased the decision-making responsibility of individual investors for their own retirement planning. With this shift comes increasing evidence that investors are making poor decisions in choosing how much to save for retirement and in selecting among their investment options. Studies question the value of efforts to improve these decisions through regulatory reforms or investor education. This article posits that deficiencies in workplace retirement savings cannot be adequately addressed until the reasons for poor investment decisions are better understood. We report the results of an exploratory study that asked subjects to complete a simulated retirement investment task and collected information about their financial knowledge and preferences. The study enabled us to measure financial literacy and evaluate its relationship to retirement investment decision-making. In line with existing research, we found a strong relationship between financial literacy and successful retirement investing. Our results suggest, however, that the relevant understanding in this context is not about math so much as it is a basic knowledge of the relative costs and benefits of the major investment categories. Finally, we present results suggesting that financial literacy is separate from investment preferences - specifically, that tolerance for risk is a separate and highly predictive variable in estimating retirement planning success. Our research suggests that individual employees are likely to lack the skills necessary to support the current regulatory model of participant-directed retirement investing. The structure and regulation of retirement plans ought to take this fact seriously. We explore the potential for investor education and professional advice, respectively, to overcome the limitations of individualized choice.
urn:nbn:de:hebis:30:3-420723
Keywords: 330